Sexual Dissidence as Dissensus in Chilean Activism: Cuds S Experience - Jara-Reyes, R (UNIV TALCA, INST ESTUDIOS HUMANISTICOS JUAN IGNACIO MOLINA, 2025)
In this article, the distinction between sexual diversity and sexual dissidence will be explored, focusing on the analysis of an activist experience: the formation and deployment of the Colectivo Universitario de Disidencia Sexual (CUDS) in the context of the 2000s. From a contextualization of the actions carried out and the premises that guided them, the article discusses the implications of using the notion of sexual dissidence to implement a politics of the name for sexual dissidence. The thesis of a gradual installation of the concept is thus defended, which is not without consequences for current debates. The introduction of this concept in the first constitutional proposal can, in this way, be linked to the process of emergence of the concept that is presented here.